Pengaruh Kualitas Pelayanan, Keragaman Produk, dan Harga terhadap Keputusan Pembelian di Perdana Stationery Kediri - Enggal Fatwa Arifiana; Ustadus Sholihin; Nurali Agus Najibul Zamzam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the extent to which service quality, product variety, and price influence purchasing decisions at Perdana Stationery Kediri. A quantitative research method was employed, involving a total of 170 respondents who were selected using accidental sampling techniques. The primary data were gathered through a structured Likert-scale questionnaire, and then analyzed using multiple linear regression analysis to assess both the individual and simultaneous effects of the independent variables on purchasing decisions. The results of the partial tests showed that service quality has a positive and significant influence on purchasing decisions, with a t-value of 4.112 and a significance level of 0.000. Similarly, product variety demonstrated a significant positive effect (t = 3.905, p = 0.000), indicating that a wide selection of products can attract and retain more customers. Furthermore, price was also found to significantly influence purchasing decisions (t = 3.732, p = 0.000), suggesting that competitive and reasonable pricing remains an essential factor in consumers' buying behavior. The simultaneous test (F-test) showed that all three variables collectively have a significant impact on purchasing decisions, with an F-value of 45.672 and a significance value of 0.000. The model explains 45.1% of the variance in purchasing decisions, indicating a substantial level of influence. In conclusion, this study highlights that delivering high-quality service, offering diverse product options, and maintaining competitive pricing are key strategies for increasing customer purchasing decisions, improving market competitiveness, and fostering long-term customer loyalty.